Complete Genome Sequence of the Exopolysaccharide-Producing Burkholderia caribensis Type Strain MWAP64 - Pan, Yanling (Genome Announc, 2016)
We report the complete genome sequence of Burkholderia caribensis MWAP64 (LMG 18531), which was isolated from soil for its proficiency in producing large amounts of exopolysaccharide that help form microaggregates in a vertisol. There are four replicons with a total size of 9,032,119 bp.